Differences between winning and defeated teams at the cadet state championship of Bosnia and Herzegovina in water polo - Lemeš, D.; Mirvic, E.; Dizdar, A.; Baždarevic - Rašidagic, A. (Sportski Logos, 2020)
The aim of this paper is to determine the differences between certain segments of the water polo game of the winning and defeated teams at the state championship of Bosnia and Herzegovina for cadets. By analyzing the results of the research on a sample of 7 teams in 21 games from the state championship of Bosnia and Herzegovina in water polo for the cadet category, we came to the conclusion that there is a statis-tically significant difference between winning and losing teams. 19 variables were tested on this sample, and they are: Goals scored, goal attempts, goals from the action, 6 on 5, goal from 6 on 5, shot from 6 on 5, goals from the anchor, penalty, penalty goal, defended penalty, counter foul, counterattack, goal from counterattack, ball sprint, shot from foul, goal from foul, Intercepted balls, corners and goal frame. It can be concluded that the results, even if they are quite similar, there was a small statistically significant difference, which shows that all teams are of approximate qualities when it comes to motor skills, techniques and tac-tics. It is recommended that a more efficient plan and program be developed to improve these capabilities as well as coach training for this Olympic sport.